2021
DOI: 10.52547/ijn.34.131.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Written Emotional Disclosure on the Stress of Mothers of Children with Autism

Abstract: Background & Aims: Autism spectrum disorder is a complex neurodevelopmental disorder whose clinical manifestations include impaired social communication, behaviors, interests, and limited and repetitive activities. Poor eye communication, lack of emotion or social interaction, impaired use of non-verbal behaviors, and lack of age-appropriate communication are the main manifestations of this disorder. This disorder is one of the main causes of disability in children under 5 years old. The exact cause of this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…The results of the studies by Ebadi et al (2021) and Ashley et al (2011) also showed that the disclosure of written emotions caused an increase in stress in caregivers or did not have an effect on reducing the psychological distress of informal caregivers, which is not in line with the present study. This difference can be interpreted in such a way that people deeply understand their problems by writing down their feelings, and with the disappearance of mental distractions, they are more affected and thus experience higher levels of stress (Ashley et al, 2011;Ebadi et al, 2021).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The results of the studies by Ebadi et al (2021) and Ashley et al (2011) also showed that the disclosure of written emotions caused an increase in stress in caregivers or did not have an effect on reducing the psychological distress of informal caregivers, which is not in line with the present study. This difference can be interpreted in such a way that people deeply understand their problems by writing down their feelings, and with the disappearance of mental distractions, they are more affected and thus experience higher levels of stress (Ashley et al, 2011;Ebadi et al, 2021).…”
Section: Discussioncontrasting
confidence: 94%
“…In this regard, a study was conducted by Mirzazadeh et al (2015) which showed that holding debriefing sessions for describing stressful events can have a positive impact on nurses' moral distress. However, some studies reported different results, such as the study by Ebadi et al (2021), where it was found emotion disclosure through writing increases the stress among the mothers of the children with autism. It should be noted that other studies had different target populations such as the mothers of autistic children, and the type of events had been different as well; Mirzazadeh's study investigated the expression of stressful incidents.…”
Section: Introductionmentioning
confidence: 99%